PEMANFAATAN APLIKASI MICROSOFT POWERPOINT PADA SISWA SMP KELAS VIII DALAM PEMBELAJARAN KOORDINAT KARTESIUS - Sofia Nurul Hikmah; Sugama Maskar (Universitas Teknokrat Indonesia, 2020)
AbstractLearning mathematics is very important for students, based on the learning objectives of mathematics in primary to secondary education, namely to prepare students to always develop logically, rationally, critically, accurately, honestly, efficiently and effectively in the world of education. The media can increase and direct the attention of students so that it can lead to learning motivation, more direct interaction between students and their environment and the ability of students to learn on their own according to their abilities. Therefore we need a learning media that can visualize objects from cartesian coordinate material. One such visual media is Power Point which can be used to visualize work objects from mathematics. This study aims to produce learning media that can be understood by students and to determine student interest in learning by using a microscope-based powerpoint learning media on cartesian coordinate material. The method used in research is research and development and the collection technique used is direct observation. The results of trials conducted, Microsoft PowerPoint based learning media were able to attract student interest in learning.Keywords: Microsoft Powerpoint, cartesian coordinate.